Triple Button Line Implementation Through Corporate Social Responsibilty Program at PT. Semen Tonasa - Nur Sandi Marsuni; Darwis Said; Aini Indrijawati (Economos : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to explain and interpret the Corporate Social Responsibility practices of PT Semen Tonasa (Persero) Tbk which are implemented in the "TJSL Pillars" program, one of the pillars of which is SEMEN TONASA. Tonasa Independent Village. This study uses a descriptive qualitative approach. Data retrieval using literature review analysis techniques. The research data was obtained from the official website of PT. Semen Tonasa which publishes every work program carried out by the company. This study found that, firstly, the company carried out a Triple Buttonline program with a Planet core which was realized in the form of being responsible for the environment, Second, the company carried out a Triple Buttonline program with a People core which was realized in the form of providing humanitarian assistance, (Healthy Tonasa and Smart Tonasa, Mandiri Tonasa , Bina Mitra Tonasa) assistance aimed directly at the development of the community who live around the company where the company operates, the three Triple Buttonline Programs at the core of Profit are realized in the form of selling products produced by PT Cement Tonasa.